КАСБИЙ-ТЕХНИКАВИЙ ТАЪЛИМДА КОМПЕТЕНЦИЯВИЙ ЁНДАШУВ - Набиев, А. (SCIENCE and SOCIETY, 2020)
This article sets out modern requirements for competitive engineering and technical personnel in the framework of a competency-based approach to the theory and practice of education in the modern information economy in the world. It also explains the forms and content of the competency-based approach (module), in the course “Material Resistance”.